Data Mining and Sharing to Create Usable Knowledge, Implementation in Small Business in Indonesia (Sains Humanika, 2021)
Data mining is one of the current methods for a company to create new knowledge from the mass amount of information source and organized it into usable data for the company's specific target. Conventionally, only large corporation uses data mining as it needs to collect massive amounts of data and process to sort it into usable forms of information; also because it has necessary customer base and target value that justified the cost and effort. However, with the growth of internet usage and web based technology, with its low barrier entry and almost cost free nature, a small company at current time should also be able to take advantage of data mining to reach its target. The paper will show some possible proposed model of data mining suitable for use by small companies in Indonesia and some of its perceived advantages.
Keywords: Data mining; knowledge management; small business